Shades of Comfort: Privacy and the Street - Kingery-Page, Katie (My University, 2010)
Conditions of pedestrian comfort have been evaluated by other researchers as they relate to climate, protection from vehicles, and spatial conditions of the street. But in a discourse that emphasizes the public nature of the street, privacy is seldom addressed. A person’s ability to regulate privacy, both in seclusion and in public, is an aspect of personal freedom. Privacy occurs and is necessary in public space, especially in dense urban environments, where privacy indoors may be limited. Privacy is a complex phenomenon dependant above all upon the individual’s desired level of privacy. The researcher uses working definitions of privacy and exposure based upon social, psychological, and legal definitions. Beginning with the theory that achieving a desired level of privacy has a profound effect on the comfort of a person on the street, the researcher identifies and describes factors that allow for privacy regulation on the street. This exploratory research uses a phenomenological method of systematically noting subjective responses to the street setting.
Keywords: Privacy; Street; Streetscape; Comfort; Public space; Street types